Circadian rhythm of freshwater crab Geosesarma noduliferum (De Man, 1892) under laboratory conditions - Winda Eka Putri; Muhammad Ridwan; Tazkiana Nurul Fathiya Sofandi; Nur Azizah Maulidiyah Rahmah; Rika Raffiudin (Faculty of Mathematics and Natural Science (FMIPA), Universitas Syiah Kuala, 2026)
Geosesarma noduliferum is a semi-terrestrial freshwater crab endemic to Java, exhibits behavioral activity potentially regulated by daily light-dark cycles. This study was aimed to analyze the circadian rhythm of this crab under laboratory conditions and examine habitat preferences during diurnal and nocturnal periods. Four individuals of 2 males and 2 female crabs were collected from their natural habitat and observed in simulated habitat tanks over three days. Behavioral observations were conducted using focal sampling during six daily sessions (three in diurnal and three nocturnal), and all activities were categorized in active or passive behaviour. The results showed that active behaviors—such as exploration, feeding, and social interaction—were more frequent and prolonged during the nocturnal period, peaking at 11:00 PM. However, passive behaviors such as resting and burial were more prevalent during diurnal. Kruskal-Wallis and Dunn tests indicated significant behavioral differences between day and night periods (p<0.05). Habitat preference also varied; both sexes favoring terrestrial areas at night; during diurnal, males predominantly occupied aquatic areas while females showed a balanced distribution. This study suggests that G. noduliferum exhibits a predominantly nocturnal activity pattern.